Recipientscycle B. Kenzheev «Message. Montreal 1889» (Eurasian Journal of Philology Science and Education, 2015)
CycleB.Kenzheev"Message. Montreal1889" consistsof 12poems.Theyturnedtothe12realpeopleandhave similar composition.Each letter has biographical facts of recipients, you can find out about where and how they live, what they do.These are the peoplethat are closein spirit toKenzheev, views, so he is sincerewith them andleada frankdiscussiononvarious topics.Epistleshave a widetonalrange, from lightto deeplyricismof irony, they observedthe elementsof narrativeand philosophicalreflections.Epistles give the opportunity to the poet aesthetic interpretation of such important concepts for him, and the fate of both the poetry, friendship and creativity, history and the birthplace of man and the world.
Keywords: message; cycle; reference; recipient; subject dominant.